The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11739-010-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonic hypersensitivity is a major determinant of the efficacy of bloating treatment in constipation-predominant irritable bowel syndrome

Abstract: The pathophysiology of bloating is largely unknown, and many mechanisms have been proposed. An alteration of intestinal gas production may have a role in a subgroup of patients, but available data are conflicting. We have previously shown that hypersensitivity to colonic fermentation is associated with severe bloating in a subgroup of patients with low intestinal gas production. Accordingly, we evaluated whether modification of intestinal gas production improves bloating severity according to the presence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Rifaximin (400 mg) were administered orally twice per day for 2 weeks to IBS-D patients ( Majewski and McCallum, 2007 ; Di Stefano et al, 2011 ). They were further followed up for an additional 10 weeks after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Rifaximin (400 mg) were administered orally twice per day for 2 weeks to IBS-D patients ( Majewski and McCallum, 2007 ; Di Stefano et al, 2011 ). They were further followed up for an additional 10 weeks after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In one trial, rifaximin plus neomycin significantly improved severity of constipation and symptoms of bloating and straining for up to 4 weeks compared with neomycin plus placebo [ 111 ]. In the other trial, rifaximin significantly decreased bloating, abdominal pain, abdominal distension and flatulence compared with placebo [ 112 ]. Overall, data suggest that rifaximin is a relatively safe therapeutic option for patients with IBS-D.…”
Section: Therapeutic Options In Managing the Intestinal Microbiome Inmentioning
confidence: 99%
“…The nonsystemic antibiotic rifaximin appears to have anti-inflammatory, host-response, and gut microbiota modulatory activities [Bajaj et al 2013; Brown et al 2010; Cheng et al 2010; Debbia et al 2008; DuPont and Jiang, 2004; Hopkins et al 2014; Jiang et al 2010a, 2010b; Maccaferri et al 2010; Mencarelli et al 2010, 2011; Schrodt et al 2013; Terc et al 2014; Xu et al 2014]. Rifaximin received regulatory approval for the treatment of IBS-D in May 2015; several studies indicated a favorable efficacy and safety profile for rifaximin in IBS-D (Table 3) [Di Stefano et al 2011; Pimentel et al 2006, 2011, 2014]. The identically designed, randomized, placebo-controlled, phase III TARGET 1 and 2 studies examined the safety and efficacy of rifaximin 550 mg 3 times daily for 2 weeks in patients with IBS-D [Pimentel et al 2011].…”
Section: Newer Agents For the Treatment Of Ibsmentioning
confidence: 99%